2015
DOI: 10.1021/bm501676p
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Structure of Biocompatible Aliphatic Polycarbonates on siRNA Transfection Ability

Abstract: RNAi therapeutics are promising therapeutic tools that have sparked the interest of many researchers. In an effort to provide a safe alternative to PEI, we have designed a series of new guanidinium- and morpholino-functionalized biocompatible and biodegradable polycarbonate vectors. The impact of different functions (morpholino-, guanidinium-, hydrophobic groups) of the architecture (linear homopolymer to dumbbell-shape) and of the molecular weight of these copolymers on their capacity to form polyplexes and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 58 publications
(117 reference statements)
1
40
0
Order By: Relevance
“…as well as intracellular barriers (endocytosis, endosomal escape, and siRNA release into the cytoplasm). [16][17][18][19][20] To deliver siRNA directed against HDAC5 mRNA, we have previously developed original aliphatic polycarbonate polymers, [21][22][23][24][25] grafted with guanidine and morpholine functional groups. The guanidine function, cationic at neutral pH, is necessary for both siRNA binding and interactions with the negatively charged plasma membranes.…”
Section: -12mentioning
confidence: 99%
See 2 more Smart Citations
“…as well as intracellular barriers (endocytosis, endosomal escape, and siRNA release into the cytoplasm). [16][17][18][19][20] To deliver siRNA directed against HDAC5 mRNA, we have previously developed original aliphatic polycarbonate polymers, [21][22][23][24][25] grafted with guanidine and morpholine functional groups. The guanidine function, cationic at neutral pH, is necessary for both siRNA binding and interactions with the negatively charged plasma membranes.…”
Section: -12mentioning
confidence: 99%
“…The resulting copolymers were dried overnight under reduced pressure at room temperature. The polymer samples were characterized by SEC in THF + 2 wt % NEt 3 and 1 H-NMR in CDCl 3 to determine the macromolecular parameters, as previously described 25 . The Boc protecting groups of the guanidinium moieties were eliminated using TFA in a 5 mL stirred solution of DCM/TFA 4/1 v/v for 18 hours at room temperature.…”
Section: Typical Procedures For the Organocatalytic Rop Of Cyclic Carbmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the tedious functionalization of aliphatic polyesters by amine pendant groups, few reports are dedicated to polycationic aliphatic polyesters for gene delivery . Interestingly, Frère et al recently reported on a biodegradable polycarbonate platform bearing pendant amines (morpholine and guanidine) that when incorporated in an appropriate copolymer gives particularly good transfection efficiencies …”
Section: Applications In Drug Deliverymentioning
confidence: 99%
“…[8][9][10][11][12] Additionally, PTMC featuresv aluable mechanical softness [16] that is favorably exploited, in particular,t owards the designo fc opolymers such as the thermoplasticP TMC-bpoly(l-lactide)e lastomers. [17][18][19][20][21][22][23] Other PTMC homopolymers [24][25][26][27] and copolymers associating, in particular,p oly(ethylene glycol) (PEG) [28][29][30][31][32][33][34][35][36][37][38] or poly(glutamic acid) (PGA) [39][40][41][42][43] segments [44][45][46][47] in spontaneously self-assemblingp olymeric structures, as well as otherP C-based copolymers, [48][49][50][51][52][53] have been developed over the past decade, mainly as polymer-drug conjugates, drug delivery systems, or hydrogels.…”
Section: Introductionmentioning
confidence: 99%